PENDAMPINGAN PENYUSUNAN SOAL KOGNITIF MENGGUNAKAN MULTIPLATFORM (ASSESSMENT LINK - QUIZIZ) BAGI GURU BIOLOGI KABUPATEN TUBAN - Susantini, Endang; Puspitawati, Rinie Pratiwi; Prastiwi, Muji Sri; Bashri, Ahmad; Rahayu, Dwi Anggorowati (Jurnal ABDI: Media Pengabdian Kepada Masyarakat, 2025)
assessment are based on high school thinking skills. High school teachers who are members of the Tuban Regency MGMP experience difficulties in developing HOTS questions, such as lacking knowledge of various platforms that can be used to carry out e-assessments. The solution to solving the problems experienced is achieving an assessment as learning program combining multiplatform assessment links and Quizzes in creating HOTS questions. This community service involves MGMP Biology and the PkM biology team (University). The aim of this PKM activity is to improve skills in preparing cognitive aspect questions using multiplatform (assessment link-qiuzziz), so that good e-assessment management can improve the quality of learning both online and offline in the era of independent learning. The stages of PkM activities include Pre-Activity (Material Presentation), implementation (Workshop and Mentoring) and Simulation, Presentation and Evaluation which have been carried out online and offline. The workshop participants were 10 teachers, members of the Tuban Regency High School Biology MGMP. PkM mentoring activities are continued synchronously via Google Meet and asynchronously via Google Classroom. Participants are provided with knowledge related to the cognitive domain with the Assessment Link application; Creating HOT questions on Biology material as well as Tutorials for creating Assessment as learning based on the Quizziz platform. Assessment of PkM activities was assessed through pre-test and post-test with an average score increase of 12.4%. Eight participant response rubrics showed a range of strongly agree statements between 48.8-83.7% who felt the suitability of the material and the good allocation of training time. This service received appreciation from teachers in improving skills in using HOTS question instruments in the learning process in accordance with the stages and guidelines for writing HOTS questions.